A espada é a lei: a dominação masculina em Marcelino Freire e em Marcelo Mirisola - Carvalho, Ilca Andréa Barroso de (2023)
This research is about male domination. More specifically, about the exercise of hegemonic masculinity and its outcome for subjects who were historically despised, as seen in the works of two contemporary authors: Marcelino Freire and Marcelo Mirisola. For this purpose, the research evaluates some short stories from Amar é crime (2015), Angu de Sangue (2019) and BaléRalé: 18 improvisos (2003), by Marcelino Freire, and the work, O herói devolvido (2000), by Marcelo Mirisola. The choice of texts is due to the perception that both authors explore male characters who embody the model of masculinity defended and maintained by patriarchy, in situations that are close to non-fictional reality. However, if, on the one hand, the characters approach each other through the exercise of compulsory masculinity, on the other, they distance themselves when the social aspect arises from the context. This is because Freire composes his characters as beings resulting from a society that did not offer alternatives to be different from what they are, while Mirisola favors only the virile masculine as such, skipping the social element as responsible for male domination. Thus, in order to compare and evaluate the texts by Freire and Mirisola, situations were investigated in the short stories in which male dominance depreciates and violates women, the LGBTQIAP+ community and other males who do not fit the model established by patriarchy. In addition, it was verified how the despised subjects react in such situations, as well as the negative consequences caused by hegemonic masculinity extensive to the entire social body. To carry out the research, the theoretical framework was based on the theories of Foucault (1988), Connell (2003), Butler (2021b), Jablonka (2021), Lerner (2019), Trevisan (2021), Saffioti (1976), Beauvoir (2005) and Welzer-Lang (2001) among many other studies that contributed in the same way to the realization of this work.